RELATIONSHIP BETWEEN SLEEP QUALITY AND MEDICATION COMPLIANCE FOR HYPERTENSIVE PATIENTS AT PRIVATE HOSPITAL YOGYAKARTA - Wijayanti, Ekatrina; Marlina, Titin (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2024)
Introduction: Hypertension is often referred to as the “silent killer” and based on the 2013 Basic Health Research data, hypertension sufferers in Indonesia at the age of >18 years reached 25.8%, while the undiagnosed reached 63.2%. Research results have shown that most people have sleep disorders, resulting in the recurrence of hypertension. This research aimed to find a relationship between sleep quality and medication compliance for hypertensive patients at Private Hospital, Yogyakarta. Method: This research used a descriptive quantitative research method with a cross-sectional approach. A total of 40 hypertensive patients were taken as the research samples using an accidental sampling technique. Sleep quality was measured using the PSQI (Pittsburgh Sleep Quality Index) instrument, and compliance with medication was measured using Morisky-8. Result: Findings show that 87.5% of respondents experienced poor sleep quality, while the remaining 12.5% had good sleep quality. Regarding medication compliance, 87.5% of respondents complied with medication, while 32.5% did not. Chi square analysis showed that there was no significant relationship between sleep quality and medication adherence (p=0.523). Conclusion: there is no relationship between sleep quality and medication compliance in hypertensive patients. Based on the results of this research, future researchers are expected to take more samples, random sampling method and examine the effect of medication compliance on quality of life